Exploring Sound Waves through a Frequency Study of the Ambience Music Weightless by Marconi Union - Andriyanto, R.M. Aditya; Budiawan, Hery; Safrina, Rien; Rahman, Putri Safrani; Fredlina, Oriana Aisha; Putri, Lara Heltna Yuma (Universitas Negeri Medan, 2024)
This study explores the creation process of